A NEW LOSS FUNCTION FOR THE SELECTION OF PRODUCER SPECIFICATION LIMITS - Rosen, Scott L; Chandra, M Jeya (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper presents a new approach to deteIlDining economical values for manufacturer lower and upper specification limits using a newly derived hybrid function for expected cost. The identification and use of specification limits are essential in protecting the producer from shipping defective products that pass unnoticed due to measurement error. This cost function is composed of four parts: a generic Taguchi loss function a function for rework cost, a function for scrap cost, and a function that describes a variance to cost tradeoff. The expected cost function does not assume the process mean to be equal to the target value of the process nor is it restricted to being symmetrical. The cost function is implemented among different production systems and optimal values of manufacturer lower and upper specification limits are determined for each system.